Title-Holding Among Egba Muslims of Ogun State, Nigeria: X-Raying the Nexus Between Islam and Yoruba Culture - Owoyemi, Samuwilu Alade (IJUS | International Journal of Umranic Studies, 2022)
Title-holding was a cultural practice of Yoruba before the penetration of Islam in Egba land, an area predominantly inhabited by the Yoruba speaking people of Ogun State, Nigeria. The acceptance of Islam by the Egba reformed, to a large extent, the socio-religious and cultural lives of the people. The Yoruba cultural systems of marriage, naming and burial rites were greatly influenced and reformed by Islam. However, a good number of the Egba, who profess Islam, still retain some of their cultural beliefs and traditions. Consequently, there is a nexus of Yoruba culture and Islamic practices and rites such as marriage, naming and funerals. Such connection can also be noticed in title-holding among the people. This paper, therefore, critically appraises the fusion of the Yoruba cultural elements to the Islamic practice of the title-holding among Egba Muslims. The paper adopts the historical approach to establish the institutionalization of title-holding in Islam. It then x-rays the institution of title-holding among the people. The study also examines the similarities between the Muslim titles and the Yoruba traditional titles patterned along the traditional set up in Egba Muslim Community. Realizing the fact that title-holding has become a firmly rooted institution among the Egba Muslims, the paper posits that the practice should be restructured for better administration of the people and development of Islam in Egbaland in particular and Yorubaland in general.